Multicenter Cohort of Patients With Methicillin-Resistant Staphylococcus aureus Bacteremia Receiving Daptomycin Plus Ceftaroline Compared With Other MRSA Treatments - McCreary, Erin K; Kullar, Ravina; Geriak, Matthew; Zasowski, Evan J; Rizvi, Khulood; Schulz, Lucas T; Ouellette, Krista; Vasina, Logan; Haddad, Fadi; Rybak, Michael J; Zervos, Marcus J; Sakoulas, George; et al. (Open forum infectious diseases, 2020)
BackgroundDaptomycin and ceftaroline (DAP-CPT) have been used for persistent methicillin-resistant Staphylococcus aureus bacteremia (MRSAB), but have rarely been compared with other therapies. This study provides an exploratory analysis of patients placed on DAP-CPT vs standard of care (SOC) for MRSAB.MethodsThis is a retrospective, matched cohort study MRSAB patients at 4 hospitals in the United States. Patients receiving DAP-CPT for ≥72 hours at any point in therapy were matched 2:1 when possible, 1:1 otherwise, to SOC, first by infection source, then age and renal function. SOC was empiric treatment with vancomycin or daptomycin and any subsequent combination antibiotic(s), except for DAP-CPT.ResultsFifty-eight patients received DAP-CPT with 113 matched SOC. Ninety-six percent of SOC received vancomycin, and 56% (63/113) escalated therapy at least once in the treatment course. Twenty-four patients received DAP-CPT within 72 hours of index culture; 2 (8.3%) died within 30 days vs 14.2% (16/113) with SOC (P > .05). Subgroup analysis identified numerically lower mortality in DAP-CPT patients with a Charlson comorbidity index ≥3, endovascular source, and receipt of DAP-CPT within 72 hours of index culture. The median MRSAB duration was 9.3 vs 4.8 days for DAP-CPT and SOC, respectively. DAP-CPT was initiated on day 6 on average; after receipt of DAP-CPT, MRSAB duration was 3.3 days.ConclusionsDAP-CPT treatment is often delayed in MRSAB. Combination therapy may be more beneficial if initiated earlier, particularly in patients at higher risk for mortality. Blinded, randomized, prospective studies are needed to eliminate selection bias inherent in retrospective analyses when examining DAP-CPT vs SOC.This multicenter, retrospective, exploratory, matched study compares demographics and clinical outcomes of patients receiving daptomycin plus ceftaroline at any time in treatment course versus other therapy for MRSA bacteremia. This combination used within 72 hours of index culture may be more beneficial for survival than as salvage therapy.